PTCHD1 gene mutation/deletion: the cognitive-behavioral phenotyping of four case reports - Federica Alice Maria Montanaro; Alessandra Mandarino; Viola Alesi; Charles Schwartz; Daniela Judith Claps Sepulveda; Cindy Skinner; Michael Friez; Gabriele Piccolo; Antonio Novelli; Ginevra Zanni; Maria Lisa Dentici; Stefano Vicari; et al. (Frontiers in Psychiatry, 2024)
IntroductionX-linked PTCHD1 gene has recently been pointed as one of the most interesting candidates for involvement in neurodevelopmental disorders (NDs), such as intellectual disability (ID) and autism spectrum disorder (ASD). PTCHD1 encodes the patched domain-containing protein 1 (PTCHD1), which is mainly expressed in the developing brain and adult brain tissues. To date, major studies have focused on the biological function of the PTCHD1 gene, while the mechanisms underlying neuronal alterations and the cognitive-behavioral phenotype associated with mutations still remain unclear.MethodsWith the aim of incorporating information on the clinical profile of affected individuals and enhancing the characterization of the genotype–phenotype correlation, in this study, we analyze the clinical features of four individuals (two children and two adults) in which array-CGH detected a PTCHD1 deletion or in which panel for screening non-syndromal XLID (X-linked ID) detected a PTCHD1 gene variant. We define the neuropsychological and psychopathological profiles, providing quantitative data from standardized evaluations. The assessment consisted of clinical observations, structured interviews, and parent/self-reported questionnaires.ResultsOur descriptive analysis align with previous findings on the involvement of the PTCHD1 gene in NDs. Specifically, our patients exhibited a clinical phenotype characterized by psychomotor developmental delay- ID of varying severity. Interestingly, while ID during early childhood was associated with autistic-like symptomatology, this interrelation was no longer observed in the adult subjects. Furthermore, our cohort did not display peculiar dysmorphic features, congenital abnormalities or comorbidity with epilepsy.DiscussionOur analysis shows that the psychopathological and behavioral comorbidities along with cognitive impairment interfere with development, therefore contributing to the severity of disability associated with PTCHD1 gene mutation. Awareness of this profile by professionals and caregivers can promote prompt diagnosis as well as early cognitive and occupational enhancement interventions.